1941
DOI: 10.1149/1.3071278
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Lead Anodes in the Electrolysis of Zinc Sulfate Solutions

Abstract: The effects of impurities, either in solution or alloyed with lead, on anodic reactions in electrolytic zinc deposition were studied. The results show that the lead content of deposited zinc is due chiefly to occluded lead dioxide and the only impurities, of those investigated, that inhibited the formation of lead dioxide are cobalt as sulfate in solution, and silver alloyed with lead as anode. The degree of anodic polarization is a function of the log of the current density. It is indicated that the ratio bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1959
1959
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These two groups of researchers related the observed effects to an unspecified process occurring in preference of the conversion of lead to lead dioxide when cobalt ions are present in the electrolyte. The conclusion was that to keep the anode potential low, one needed to maintain the cobalt concentration by continuous addition of cobalt ions to the electrolyte (Koenig et al, 1941). Tsuruoka (1958) followed a similar approach to study the effect of cobalt ions in a typical zinc electrowinning system and also observed a reduction in lead dissolution when cobalt ions were present in the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…These two groups of researchers related the observed effects to an unspecified process occurring in preference of the conversion of lead to lead dioxide when cobalt ions are present in the electrolyte. The conclusion was that to keep the anode potential low, one needed to maintain the cobalt concentration by continuous addition of cobalt ions to the electrolyte (Koenig et al, 1941). Tsuruoka (1958) followed a similar approach to study the effect of cobalt ions in a typical zinc electrowinning system and also observed a reduction in lead dissolution when cobalt ions were present in the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…1. The fresh anode surface is initially covered with a non-conducting layer of PbSO 4 formed by reaction (2). PbSO 4 is oxidised to the conducting oxide PbO 2 via reaction (3)…”
Section: Introductionmentioning
confidence: 99%
“…Prior research [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] has shown that a small amount (less than 100 ppm) of cobalt ions in the electrolyte results in a lower oxidation rate of the lead alloy, a lower oxygen overpotential (or at least a lower potential of the lead), a smaller amount of PbO 2 on the lead surface [12] and mainly lead sulphate [19] as the oxidation product. The lower potential at the lead anode could lead directly to a lower oxidation rate.…”
Section: Introductionmentioning
confidence: 99%